PENGARUH PAJAK HOTEL DAN HIBURAN TERHADAP PENDAPATAN ASLI DAERAH KOTA KENDARI - Nuraeni, Nuraeni (JURNAL AKUNTANSI, 2017)
ABSTRACTThe purpose of this research is (1) To Determine The Effect of Taxes of revenue locally-generated revenue; (2) To Know the Entertainment Tax Effect Against Local Revenue; (3) To determine the simultaneous effects of hotel tax and entertainment to local revenues.These results indicate that: Tax Hotel significant positive effect on regional revenue Kendari, entertainment tax Influential Positive but not significant Against Local Revenue Kendari, and Â Taxes And Entertainment Influential Simultaneously Against Local Revenue Kendari.Keywords: Hotel Tax, Entertainment Tax, and Local Revenue.